Temptation-driven preferences - Eddie Dekel; Barton L. Lipman; Aldo Rustichini (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2006)
My own behavior baffles me. For I find myself not doing what I really want to do but doing what I really loathe. Saint Paul What behavior can be explained using the hypothesis that the agent faces temptation but is otherwise a standard rational agent? In earlier work, GulPesendorfer [2001] use a set betweenness axiom to restrict the set of preferences considered by Dekel, Lipman, and Rustichini [2001] to those explainable via temptation. We argue that set betweenness rules out plausible and interesting forms of temptation including some which may be important in applications. We propose a pair of alternative axioms called DFC, desire for commitment, and AIC, approximate improvements are chosen. DFC characterizes temptation as situations where given any set of alternatives, the agent prefers committing herself to some particular item from the set rather than leaving herself the flexibility of choosing later. AIC is based on the idea that if adding an option to a menu improves the menu, it is because that option is chosen under some circumstances. From this interpretation, the axiom concludes that if an improvement is worse (as a commitment) than some commitment from the menu, then the best commitment from the menu is strictly preferred to facing the menu. We show that these axioms characterize a natural generalization of the GulPesendorfer representation.
Keywords: 330; Präferenztheorie; Theorie